2020
DOI: 10.3390/s20226421
|View full text |Cite
|
Sign up to set email alerts
|

IRT and GPR Techniques for Moisture Detection and Characterisation in Buildings

Abstract: The integrity, comfort, and energy demand of a building can be negatively affected by the presence of moisture in its walls. Therefore, it is essential to identify and characterise this building pathology with the most appropriate technologies to perform the required prevention and maintenance tasks. This paper proposes the joint application of InfraRed Thermography (IRT) and Ground-Penetrating Radar (GPR) for the detection and classification of moisture in interior walls of a building according to its severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…It should be noted that a process of erosion and dilation [ 9 ] was applied automatically after finding the respective intersection points in each overlapping histogram and before obtaining the definitive segmenting in each next_image (i.e., before obtaining Figure 15 ). The erosion process is applied to eliminate small-size segmented areas, considered as noise, while the subsequent dilation process is applied to group the closest segmented areas into one single segmented area.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that a process of erosion and dilation [ 9 ] was applied automatically after finding the respective intersection points in each overlapping histogram and before obtaining the definitive segmenting in each next_image (i.e., before obtaining Figure 15 ). The erosion process is applied to eliminate small-size segmented areas, considered as noise, while the subsequent dilation process is applied to group the closest segmented areas into one single segmented area.…”
Section: Methodsmentioning
confidence: 99%
“…The erosion process is applied to eliminate small-size segmented areas, considered as noise, while the subsequent dilation process is applied to group the closest segmented areas into one single segmented area. In addition, each segmented area is labelled with a different index by applying a connecting method [ 9 ]. In this way, the smallest segmented areas that were not eliminated by the erosion process are automatically eliminated by counting the number of pixels in each segmented area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Tejedor et al [35] highlighted that most studies were qualitative, to discover heterogeneities due to anomalies (moisture, thermal bridges, cracks, air leakages, etc.) below the plaster [36][37][38][39][40] and to define the geometry of a masonry, among other purposes [41]. Besides this, international standards (i.e., ISO 6781:1983 [42]), UNE EN 13187:1998 [43], ASTM E1311 [44], ASTM E1862 [45], and guidelines (i.e., RESNET [32]) only recommend boundary conditions for the use of qualitative IRT tests to carry out energy audits in buildings [33,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, through the combination of both techniques, it was possible to provide an interpretation of the water displacement, from the exterior surface to the interior surface of the wall, and to provide a relative depth of water inside the wall. It was concluded that more information and greater reliability can be gained by using complementary IRT-GPR, showing the benefits of combining both techniques in the building sector [ 8 ].…”
mentioning
confidence: 99%